Work Design in the Contemporary Era - Knight, Caroline; Kaur, Sabreen; Parker, Sharon (2022)
Work design refers to the roles, responsibilities, and work tasks that comprise an individual’s job and how they are structured and organized. Good work design is created by jobs high in characteristics such as autonomy, social support, and feedback, and moderate in job demands such as workload, role ambiguity, and role conflict. Established research shows good work design is associated with work outcomes such as job satisfaction, organizational commitment, work safety, and job performance. Poor work design is characterized by roles that are low in job resources and/or overly high in job demands, and has been linked to poor health and well-being, absenteeism, and poor performance. Work design in the 20th century was characterized by traditional theories focusing on work motivation, well-being, and performance. Motivational and stress theories of work design were later integrated, and work characteristics were expanded to include a whole variety of task, knowledge, social, and work-context characteristics as well as demands, better reflecting contemporary jobs. In the early 21st century, relational theories flourished, focusing on the social and prosocial aspects of work. The role of work design on learning and cognition was also recognized, with benefits for creativity and performance.